The Calculation Of Ngancar Batuwarna Reservoir, Wonogiri, Central Java - Ulfa, Azura; Suprayogi, Slamet; Khoirullah, Evi Mivtahul (Universitas Pendidikan Ganesha, 2017)
Evaluation of reservoir capacity is needed to find out how big the effective volume change of Ngancar Reservoir from the beginning of measurement until 2016. The purpose of this research is measuring volume of Ngancar Reservoir using bathymetry method with echosounder and calculating the remaining relative age of Ngancar Reservoir. Measurement topography of Ngancar Reservoir is done by bathymetry method of aquatic systematic random sampling method through certain path using echosounder. Analysis of reservoir capacity is done by calculating the volumes of Ngancar Reservoir and calculating the residual life of the reservoir relative. Fluctuation analysis of volume change was done by calculating the effective volume of reservoirs 1946-2016 and graphs. The calculation of the volume of the Ngancar Reservoir from the topographic map produces an effective volume value of 2016 is 1269905 m3 and the effective puddle area is 1393416 m2. An increase in sedimentation volume from 2011-2016 amounted to 296119.75 m3 with sedimentation rate was 59223.95 / year. With the assumption that the same landuse and sedimentation rate tend to be stable then the remaining age of Ngancar Reservoir is 21 years and 95 years old.